Mesenteric Panniculitis: An Unusual Presentation of Abdominal Pain - Patel, Ankit (Cureus, 2019)
Sclerosing mesenteritis is a rare autoimmune disease that eventually evolves into fibrotic changes that usually affect the adipose tissue around the mesenteric vessels. It can present through a myriad of gastroenterological as well as constitutional symptoms, including but not limited to abdominal pain, diarrhea, fever, nausea, or vomiting. Although the exact etiology of the disease is yet to be determined, there are several predisposing factors, the most common of which is a previous history of abdominal trauma and/or surgery. Several case series have reported the association of sclerosing mesenteritis with prior abdominal surgery ranging from as low as 24% to as high as 53%.